Safety, tolerability, and pharmacokinetics of multiple ascending doses of naloxegol. Issue 6 (4th September 2015) - Eldon, Michael A.; Kugler, Alan R.; Medve, Robert A.; Bui, Khanh; Butler, Kathleen; Sostek, Mark
Abstract: Opioid‐induced constipation (OIC) is the most common and often a treatment‐limiting adverse event (AE) of opioid therapy for chronic pain. Naloxegol (previously NKTR‐118), a PEGylated derivative of naloxone that has minimal penetration of the central nervous system, has received regulatory approval as an oral therapy for OIC. This randomized, double‐blind, placebo‐controlled, multiple‐dose, dose‐escalation study was performed to assess safety, tolerability, and pharmacokinetics of multiple doses of naloxegol in healthy volunteers. Four cohorts, each with 4 male and 4 female volunteers, were randomized 3:1 to a twice‐daily naloxegol solution (25, 60, 125, and 250 mg) or matching placebo solution. Doses were given every 12 hours for 7 days, with a single final dose on the morning of day 8. All 32 subjects completed the study. The incidence of most AEs was similar in the naloxegol and placebo groups; no AE led to study discontinuation. Naloxegol was rapidly absorbed. Plasma naloxegol pharmacokinetics showed dose proportionality, negligible accumulation at steady state, and no sex differences. Naloxegol in doses up to 250 mg every 12 hours was generally safe and well tolerated in this healthy volunteer population.